Intestinal Morphology in Broiler Chickens Supplemented with Propolis and Bee Pollen - Ivana Prakatur; Maja Miskulin; Mirela Pavic; Ksenija Marjanovic; Valerija Blazicevic; Ivan Miskulin; Matija Domacinovic (Animals, 2019)
The aim of this study was to determine the influence of dietary supplementation with propolis and bee pollen on the intestinal morphology and absorptive surface areas of chickens. Two hundred day-old Ross 308 chickens (100 male and 100 female) were equally allocated into five groups. Throughout the whole study, the control group of chickens was fed with a basal diet, while the experimental groups of chickens were fed with the same diet supplemented with propolis and bee pollen: P1 = 0.25 g of propolis/kg + 20 g of bee pollen/kg; P2 = 0.5 g of propolis/kg; P3 = 1.0 g of propolis/kg; P4 = 20 g of bee pollen/kg. The duodenal villi of chickens from all experimental groups were significantly higher and wider (p < 0.001), while their duodenal villi crypts were significantly deeper (p < 0.001) in comparison with these parameters in chickens from the control group. The villus height to crypt depth ratio, as well as the absorptive surface areas of broiler chickens, were significantly increased (p < 0.001) in experimental groups of chickens in comparison with the control group. These findings suggest that dietary supplementation with propolis and bee pollen has a beneficial effect on broilers chickens’ intestinal morphophysiology.